2006
DOI: 10.1128/aem.01174-06
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Supports the Hypothesis that Cow- and Human-AssociatedSalmonellaIsolates Represent Distinct and Overlapping Populations

Abstract: A collection of 179 human and 156 bovine clinical Salmonella isolates obtained from across New York state over the course of 1 year was characterized using serotyping and a multilocus sequence typing (MLST) scheme based on the sequencing of three genes (fimA, manB, and mdh). The 335 isolates were differentiated into 52 serotypes and 72 sequence types (STs). Analyses of bovine isolates collected on different farms over time indicated that specific subtypes can persist over time on a given farm; in particular, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
68
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 45 publications
13
68
1
Order By: Relevance
“…On the other hand, Salmo- nella characterization methods that allow for phylogeny reconstruction (e.g., MLST) might provide some advantages over traditional or molecular serotyping approaches, which do not provide phylogenetic information. For example, MLST can differentiate isolates into distinct phylogenetic groups even if they represent the same serovar, and this has been demonstrated for a number of polyphyletic serovars (51).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Salmo- nella characterization methods that allow for phylogeny reconstruction (e.g., MLST) might provide some advantages over traditional or molecular serotyping approaches, which do not provide phylogenetic information. For example, MLST can differentiate isolates into distinct phylogenetic groups even if they represent the same serovar, and this has been demonstrated for a number of polyphyletic serovars (51).…”
Section: Discussionmentioning
confidence: 99%
“…While traditional MLST schemes target seven housekeeping genes (24), we initially used a previously reported MLST scheme targeting three genes (i.e., manB, mdh, and fimA) (2,33) to characterize all isolates used in this study. In addition to these three genes, we also sequenced an 826-nucleotide fragment of a fourth gene (aroC) in all isolates to determine whether the use of additional genes would increase discriminatory power.…”
Section: Salmonella Isolates a Total Of 190 Salmonella Isolates Initmentioning
confidence: 99%
“…Salmonella serotype 4,5,12:i:Ϫ has been isolated, particularly over the last decade, from a number of different foods and animals (1,6,13,29,38). While a number of separate studies, using molecular subtyping and characterization tools (e.g., genomic microarrays and PCR assays to test for gene presence/absence), have shown that Salmonella serotype 4,5,12:i:Ϫ isolates from Spain (15,18) and the United States (1,2,38) are genetically closely related to Salmonella serotype Typhimurium, we are not aware of any comparative studies of Salmonella serotype 4,5,12:i:Ϫ isolates from Europe and the United States that have been published to date. In order to provide a better understanding of the transmission, ecology, and evolution of Salmonella serotype 4,5,12:i:Ϫ, we have assembled a collection of 190 Salmonella serotype 4,5,12:i:Ϫ and Typhimurium isolates from various sources and from two countries, the United States and Spain.…”
mentioning
confidence: 99%
“…"content-markup(./author-grp [1]/aff|./author-grp [1]/dept-list)> Salmonella is one of the most common food-borne pathogens in the United States, with 40,000 confirmed cases reported annually and subclinical infections estimated at 1.2 million per year (http://www.cdc.gov/salmonella/). 1,16 According to surveillance conducted by the Centers for Disease Control and Prevention (CDC) on food-borne illnesses confirmed in 2006, Salmonella infections accounted for 25.6% of hospitalizations and 30.6% of deaths due to food-associated intoxications; thus, these infections represent a significant public health concern. 6,14,16,20,23 Of the Salmonella isolates from human cases of food poisoning in 2005 identified by the CDC's FoodNet, 6 serovars accounted for 61% of isolates recovered: Typhimurium (19%), Enteritidis (18%), Newport (10%), Heidelberg (6%), Javiana (5%), and Salmonella 4,5,12 (3%), all of which have been isolated from animals.…”
mentioning
confidence: 99%
“…?show "fnote_aff1"$^! "content-markup(./author-grp [1]/aff|./author-grp [1]/dept-list)> Salmonella is one of the most common food-borne pathogens in the United States, with 40,000 confirmed cases reported annually and subclinical infections estimated at 1.2 million per year (http://www.cdc.gov/salmonella/). 1,16 According to surveillance conducted by the Centers for Disease Control and Prevention (CDC) on food-borne illnesses confirmed in 2006, Salmonella infections accounted for 25.6% of hospitalizations and 30.6% of deaths due to food-associated intoxications; thus, these infections represent a significant public health concern.…”
mentioning
confidence: 99%